Designing a Course on Audio Description and Defining the Main Competences of the Future Professional - Matamala, Anna; Orero, Pilar (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Considering Audio Description as a type of intersemiotic translation, and being aware of future opportunities in this field once laws are enforced, a course on Audio Description has been developed within the MA in Audiovisual Translation at the Universitat Autònoma de Barcelona (UAB), compelling us to define the main competences a future professional in audio description will have to acquire. In this article, the skills put forward by various academics and professionals are analysed in order to establish the main competences that should be acquired by an audio describer, and sample activities that are used in class are discussed.